2004
DOI: 10.1038/ni1060
|View full text |Cite
|
Sign up to set email alerts
|

TLR-independent control of innate immunity in Caenorhabditis elegans by the TIR domain adaptor protein TIR-1, an ortholog of human SARM

Abstract: Both plants and animals respond to infection by synthesizing compounds that directly inhibit or kill invading pathogens. We report here the identification of infection-inducible antimicrobial peptides in Caenorhabditis elegans. Expression of two of these peptides, NLP-29 and NLP-31, was differentially regulated by fungal and bacterial infection and was controlled in part by tir-1, which encodes an ortholog of SARM, a Toll-interleukin 1 receptor (TIR) domain protein. Inactivation of tir-1 by RNA interference ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
471
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 438 publications
(484 citation statements)
references
References 43 publications
11
471
0
2
Order By: Relevance
“…10 Although its role in anti-bacterial defense is unknown, it is co-regulated with TIR-1, which is important to the defense of Caenorhabditis elegans against bacterial infections. 11 An activator of caspase-mediated apoptosis, TNFSF10 (TRAIL), is a cytokine that belongs to the tumor necrosis factor (TNF) ligand family. It was strongly upregulated at the first time point.…”
Section: Resultsmentioning
confidence: 99%
“…10 Although its role in anti-bacterial defense is unknown, it is co-regulated with TIR-1, which is important to the defense of Caenorhabditis elegans against bacterial infections. 11 An activator of caspase-mediated apoptosis, TNFSF10 (TRAIL), is a cytokine that belongs to the tumor necrosis factor (TNF) ligand family. It was strongly upregulated at the first time point.…”
Section: Resultsmentioning
confidence: 99%
“…TIR-1 was hypothesized to mediate signaling from TOL-1, which is the only TLR homologue. Indeed, knockdown of tir-1 shortened the lifespan of worms feeding on Drechmeria coniospora , Serratia marcescens ( 16 ), Pseudomonas aeruginosa, and Enterococcus faecalis ( 17 ). However, this eff ect was independent of TOL-1 ( 16 ).…”
Section: Myd88-5 Is Expressed In Neuronsmentioning
confidence: 96%
“…Indeed, knockdown of tir-1 shortened the lifespan of worms feeding on Drechmeria coniospora , Serratia marcescens ( 16 ), Pseudomonas aeruginosa, and Enterococcus faecalis ( 17 ). However, this eff ect was independent of TOL-1 ( 16 ). Thus, rather than mediating signaling from TOL-1, TIR-1 may have controlled recognition of environmental cues derived from the pathogenic bacteria.…”
Section: Myd88-5 Is Expressed In Neuronsmentioning
confidence: 99%
“…Subsequent functional analysis in silico showed that 9.5% of SSGs and 31.5% of GSGs have been annotated and classified. Among the annotated LSGs, the proteins (F-box protein, C-type lectin, Caenacin, insulin-like peptide, C. elegans homeobox, and neuropeptide-like protein) related to sex determination [32], specific stress [36], immune response [34,35,38,40], growth factor [39], morphogenesis [31,33], and behavior [37] are considerably over-represented in LSGs. For previously unannotated LSGs, we used ProtFun2.2 to predict their functions (cellular roles and GO categories).…”
Section: Discussionmentioning
confidence: 99%
“…We classified them into different groups based on gene class description and calculated the gene number in each group. The results indicated that the functions, related to sex determination, specific stress, immune response, growth factor, morphogenesis, and behavior [31][32][33][34][35][36][37][38][39][40] The vertical axis represents the proportion of genes with each exon-intron structure compared with total SSGs, GSGs, or ECs (evolutionarily conserved genes), whereas, the abscissa axis represents the types of exon-intron structure.…”
Section: Presumed Functions Of Ssgs and Gsgsmentioning
confidence: 99%